Compressive and shear strength of coarse silt stabilized with Terramix F22.5 binder - Katarzyna Kamińska (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The paper presents the results of testing the compressive strength, frost resistance and shear strength of stabilized fine-grained soil depending on the added hydraulic binder and the time and method of curing. Determination of these parameters was to check the suitability of the soil for stabilization purposes.